Спростування російських історичних міфів та протидія ворожій пропаганді в студентському середовищі - Старжець, Володимир Іванович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
In the conditions of modern Russian aggression, social science education acts as the basis of historical memory, national consciousness, legal culture, and education of dignity in the younger generation. History in higher education has significant opportunities for the formation of modern historical memory in the younger generation of Ukrainians. The refutation of Soviet-Russian historical myths in the process of teaching in higher education will contribute to the development of critical thinking and the formation of students’ objective knowledge about the representation of our past. An important task of the educational process in higher education is to counter Russian historical myths and propaganda and at the same time to form a Ukrainian-centric view of one’s own history.